Balancing the Tides Marine Practices in American Samoa - Poblete, JoAnna (University of Hawai'i Press, 2020)
"Balancing the Tides highlights the influence of marine practices and policies in the unincorporated territory of American Samoa on the local indigenous group, the American fishing industry, international seafood consumption, U.S. environmental programs, as well as global ecological and native concerns. Poblete explains how U.S. federal fishing programs in the post-World War II period encouraged labor based out of American Samoa to catch and can one-third of all tuna for United States consumption until 2009. Labeled Made in the USA, this commodity was sometimes caught by non-U.S. regulated ships, produced under labor standards far below continental U.S. minimum wage and maximum work hours, and entered U.S. jurisdiction tax free. The second half of the book explores the tensions between indigenous and U.S. federal government environmental goals and ecology programs. Whether creating the largest National Marine Sanctuary under U.S. jurisdiction or collecting basic data on local fishing, initiatives that balanced western-based and native expectations for respectful community relationships and appropriate government programs fared better than those that did not acknowledge the positionality of all groups involved. Despite being under the direct authority of the United States, American S?moans have maintained a degree of local autonomy due to the Deeds of Cession signed with the U.S. Navy at the turn of the twentieth century that created shared indigenous and federal governance in the region. Balancing the Tides demonstrates how western-style economics, policy-making, and knowledge building imposed by the U.S. federal government have been infused into the daily lives of American S?moans. American colonial efforts to protect natural resources based on western approaches intersect with indigenous insistence on adhering to customary principles of respect, reciprocity, and native rights in complicated ways. Experiences and lessons learned from these case studies provide insight into other tensions between colonial governments and indigenous peoples engaging in environmental and marine-based policy-making across the Pacific and the globe. This study connects the U.S.-American S?moa colonial relationship to global overfishing, world consumption patterns, the for-profit fishing industry, international environmental movements and studies, as well as native experiences and indigenous rights. Open Access publication of this book was made possible by the Sustainable History Monograph Pilot, an initiative sponsored by the Andrew W. Mellon Foundation."